Alginate hydrogel matrix stiffness influences the in vitro development of caprine preantral follicles. Issue 7 (25th April 2014) - Brito, I.R.; Silva, C.M.G.; Duarte, A.B.G.; Lima, I.M.T.; Rodrigues, G.Q.; Rossetto, R.; Sales, A.D.; Lobo, C.H.; Bernuci, M.P.; Rosa‐e‐Silva, A.C.J.S.; Campello, C.C.; Xu, M.; et al.
SUMMARY This study examined caprine follicular development in different concentrations of alginate matrix to determine the optimal conditions for culture. Caprine preantral follicles were cultured in a two‐dimensional system (control) or a three‐dimensional encapsulated system in 0.25%, 0.5%, or 1% alginate (ALG 0.25, ALG 0.5, and ALG 1, respectively). A higher percentage of morphologically normal follicles developed in ALG 0.5 and ALG 1 than in ALG 0.25 or the control (P < 0.05). The rate of antrum formation, however, was higher in ALG 0.25 than in ALG 0.5 and ALG 1 conditions (P < 0.05), but similar to the control. Follicles cultured in ALG 0.25 had higher growth rates and meiotic resumption than those cultured in ALG 0.5, ALG 1, or the control (P < 0.05). Moreover, follicles cultured in ALG 0.25 had higher levels of estradiol and progesterone than those cultured in ALG 0.5, ALG 1, or the control, as well as higher levels of CYP19A1 and HSD3B mRNA. In conclusion, a three‐dimensional system that uses ALG 0.25 fosters the in vitro development of caprine preantral follicles and increases the rate of meiotic resumption. Mol. Reprod. Dev. 81: 636–645, 2014. © 2014 Wiley Periodicals, Inc.